2021
DOI: 10.1128/spectrum.00727-21
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Distribution of WhiB- and Lsr2-Type Regulators in Actinobacteriophage Genomes

Abstract: Actinobacteriophages are viruses that infect bacterial species of the diverse phylum of Actinobacteria. Phages engage in a close relationship with their bacterial host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Finally, we note that lsr2 homologues are present in many actinobacteriophage genomes including those of Mycobacterium , Gordonia , Streptomyces and Microbacterium 54 , 55 (Fig. 6a ), raising the possibility that phages encode these to counter host defence mechanisms involving loss of Lsr2 activity.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we note that lsr2 homologues are present in many actinobacteriophage genomes including those of Mycobacterium , Gordonia , Streptomyces and Microbacterium 54 , 55 (Fig. 6a ), raising the possibility that phages encode these to counter host defence mechanisms involving loss of Lsr2 activity.…”
Section: Resultsmentioning
confidence: 99%
“…For Ankus, Byblos, and DekoNeimoidia infecting S. griseus , a gene coding for a DNA polymerase exonuclease subunit was found as well. Interestingly, Mandalore and Naboo harbour a gene coding for an FtsK-like protein, and Ankus, Byblos, DekoNeimoidia, and Naboo additionally encode WhiB-like and Lsr2-like transcriptional regulators, which are widespread in actinophages (Sharma et al, 2021). All genomes contain almost 80% of hypothetical proteins, emphasizing the large amount of ‘dark matter’ in actinobacteriophage genomes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Ankus, Byblos, DekoNeimoidia, Mandalore, and Naboo encode FtsK-like, Lsr2-like, and WhiB-like proteins known from host regulatory networks in Streptomyces , and which are found in many other actinobacteriophages (Bush, 2018; Chen and Banfield, 2024; Hardy et al, 2020; Sharma et al, 2021). Some other genomic features include a MazG-like pyrophosphatase in phage Mandalore, potentially interfering with the host abortive infection mechanism (Gross et al, 2006; Harms et al, 2018) and a Cas4 family exonuclease encoded by Naboo that could lead to host spacer acquisition and subsequently autoimmunity of the bacterial host (Hooton and Connerton, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…5). A previous study of our group identified WhiB-(pfam02467) and Lsr2-type (pfam11774) regulators as most abundant transcriptional regulators encoded by actinobacteriophages genomes 51 . This is in line with the analysis of prophage genomes, where we found WhiB among the top twenty domains (Lsr2 at position 80, see Supplementary Tables S7, S8).…”
Section: Genomic Comparison Reveals a Remarkable Phylogenetic Diversi...mentioning
confidence: 92%